Restaurant tipping in Europe: a comparative assessment. Issue 6 (19th March 2021) - Gössling, Stefan; Fernandez, Sébastien; Martin-Rios, Carlos; Reyes, Susana Pasamar; Fointiat, Valérie; Isaac, Rami K.; Lunde, Merete
ABSTRACT: Tipping is a social norm in many countries and has important functions as a source of income, with significant social welfare effects. Tipping can also represent a form of lost tax revenue, as service workers and restaurants may not declare all cash tips. These interrelationships remain generally insufficiently understood. This paper presents the results of a comparative survey of resident tipping patterns in restaurants in Spain, France, Germany, Switzerland, Sweden, Norway, and the Netherlands. ANOVA and ANCOVA analyses confirm significant variation in tipping norms between countries, for instance with regard to the frequency of tipping and the proportion of tips in relation to bill size. The paper discusses these findings in the context of employment conditions and social welfare effects, comparing the European Union minimum wage model to gratuity-depending income approaches in the USA. Results have importance for the hospitality sector and policymakers concerned with social welfare.